Against redemption: The dilemma of memoir - Robertson, Rachel (University of Canberra, 2012)
The pressure for commercially published memoirs to offer a tragedy-to-triumph redemptive arc is exacerbated when the memoir is about disability. I explore how I attempted to contest this narrative arc, using a thematic rather than chronological approach and adopting the personal essay form. I also unpack the role of metaphor in representing a disability such as autism and the complexities of writing from a socio-cultural (rather than symbolic or medical) paradigm of disability. I examine one of the key dilemmas of writing a relational memoir and the creative judgements that the author must make.